Biosorption of Cr(VI) from AqueousSolution Using New Adsorbent: Equilibrium and Thermodynamic Study - Israa G. Zainal (E-Journal of Chemistry)
Biosorption is one such emerging technology which utilized naturally occurring waste materials to sequester heavy metals from polluted water. In the present study cinnamon was utilized for Cr(VI) removal from aqueous solutions.It was found that a time of two hours was sufficient for sorption to attain equilibrium. The optimum pH was 2 for Cr(VI) removal. Temprature has little influence on the biosorption process. The Cr(VI) removal decreased with increase in temperature. The biosorption data was well fitted to Dubinin - Radushkevich (D-R), Freundlich and Tempkin adsorption isotherm models, although the correlation coefficient of Langmuir model was high but the calculated adsorption capacity did not agree with the experimental. The thermodynamic study reveals that the biosorption process is spontaneous and the spontaneity decreased with temperature increase and the process is exothermic accompanied by highly ordered adsorbate at the solid liquid interface. ΔH° values were negative and lie in the range of physical adsorption.